Changes in the Anatomic and Microscopic Structure and the Expression of HIF-1α and VEGF of the Yak Heart with Aging and Hypoxia. - Yanyu He; Sijiu Yu; Junwei Hu; Yan Cui; Penggang Liu (PLoS ONE, 2016)
The study aimed to identify the changes of anatomic and microscopic structure and the expression and localization of hypoxia-inducible factor (HIF)-1α and vascular endothelial growth factor (VEGF) in the myocardium and coronary artery of the yak heart adapted to chronic hypoxia with aging. Thirty-two yaks (1 day, 6 months, 1 year, 2 years, and 5 year old) were included, and immunoelectronmicroscopy, immunohistochemistry, and enzyme-linked immunosorbent assay (ELISA) were used. Right ventricular hypertrophy was not present in yaks with aging. There was no intima thickening phenomenon in the coronary artery. The ultrastructure of myofibrils, mitochondria, and collagen fibers and the diameter and quantity of collagen changed significantly with aging. The enzymatic activity of complexes I, II, and V increased with age. Immunogold labeling showed the localization of HIF-1α protein in the cytoplasm and nuclei of endothelial cells and cytoplasm of cardiac muscle cells, and VEGF protein in the nuclei and perinuclei areas of smooth muscle cells of coronary artery, and in the cytoplasm and nuclei of endothelial cells. ELISA results showed that HIF-1α secretion significantly increased in the myocardium and coronary artery from an age of 1 day to 2 years of yaks and decreased in old yaks. However, VEGF protein always increased with aging. The findings of this study suggest that 6 months is a key age of yak before which there are some adaptive changes to deal with low-oxygen environment, and there is a maturation of the yak heart from the age of 6 months to 2 years.